Study on the Cultivation of Medical Teachers' Digital and Intelligent Literacy Based on Stigler's Technical Thought - Licong WANG; Xiaoqi SUN; Zhenhua RONG; Gang WANG; Jing XIAO (Yixue yu zhexue, 2025)
Medical education has undergone significant changes thanks to the widespread of digital and intelligent technology, making the digital and intelligent literacy of medical teachers a crucial aspect of medical education development. This paper begins by examining the challenges faced by medical teachers across four dimensions: subject, object, the subject-object relationship, and spatiotemporal contexts. Based on Stigler's technical philosophy, the cultivation path involving policy support, education reform, resource coordination, promotion of technological culture, and ethical-legal safeguards is proposed. The goal is to provide theoretical support and practical reference for medical teachers to acclimate digital and intelligent teaching models, thereby advancing the modernization of the entire medical education system, enhancing social and technical culture, and fostering innovation and development in medical education.